SLM-based interferometer for assessing the polychromatic neural transfer function of the eye - Suchkov, Nikolai; Kurian, Tobin; Schwarz, Christina; Leube, Alexander; Wahl, Siegfried (Biomedical optics express, 2021)
A novel interferometric instrument for measuring neural transfer function (NTF) of the eye is presented. The device is based on a liquid-crystal-on-silicon spatial light modulator (SLM), which is used to create two laterally separated wavefronts in the pupil plane of the eye that interfere on the retina. The phase mask on the SLM, consisting of two diffraction gratings mixed in a checkerboard pattern and acting as a shearing interferometer, allows independent control of spatial frequency, orientation, and contrast of the fringes, as well as the field of view in a wide polychromatic spectrum. Coupled with a supercontinuum source, the system is able to produce achromatic fringes on the retina. The instrument was successfully tested in six normal subjects in four light conditions: polychromatic light and monochromatic blue, green and red light respectively (central wavelengths - 450, 550 and 650 nm). On average, the NTF in polychromatic light was approximately 20% higher than for green and red light, although not statistically significant due to high intersubject variability. Due to all-digital control of the interference fringes, the device is optically simple and virtually unsusceptible to vibrations, allowing its use in a non-laboratory environment. The study also contributes to color vision research, allowing to evaluate contrast sensitivity function without monochromatic or chromatic aberrations.